(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
National Conference on ‘Importance of Inter-Disciplinary Studies in Higher Education in the Areas of Engineering, Science, Management and Humanities (2018)Organized by IMPARC, Pune, Maharashtra